(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate whether the addition of a combination of probiotics (PROB) and prebiotics (PREB) or both alone in the diet of Holstein calves after lactation has a positive effect on the immune and antioxidant response capable of favoring the animal’s growth. Eighteen Holstein animals (79.2 kg and 70 days old), housed in individual pens for 92 days were used here, and divided into three treatments: PROB (n=6), PREB (n=6) and PROB+ PREB (n=6). The consumption of PREB and the association PREB+PROB generated a gain in body weight about 10% more than PROB. In the blood count, the only change was the treatment x day interaction for monocyte counts, being higher on days 63 and 92 in the blood of the PREB and PROB animals, respectively, compared to the other groups. The PREB + PROB association from day 63 increased the activity of the glutathione S-transferase enzyme by 14% when compared to the consumption of only PREB, in addition to reducing the levels of TBARS in the blood by 35%. Furthermore, the association of PREB+PROB reduced by 12.5% and 16.2% the concentration of serum urea in relation to PREB and PROB, respectively. Animals in the PREB+PROB group had higher serum IgA levels compared to the PROB, contrary to what happened with the heavy chain IGG levels, that is, it was higher in the PROB compared to the PREB+ PROB association. On day 63, lower levels of haptoglobin were observed in PREB compared to the other groups. On day 92, lower levels of transferrin and acid glycoprotein were observed in the blood of animals that consumed PREB+PROB. Also on day 92, serum ceruplasmin levels in PROB were higher than in PREB animals. A higher of apparent digestibility coefficient (ADC) of organic matter (OM) was observed when the animal’s consumed prebiotic compared to probiotic, and the association of both did not differ from the two treatments for ADC of OM. The results allow us to conclude that the PREB+PROB association was important to minimize the physiological oxidative stress, as well as to raise the serum levels of IgA, an important mucosal immunoglobulin at the level of the digestive system; in addition, the combination of physiological results of prebiotic consumption alone or in combination reflected in greater weight gain in calves.